A case study of the digital literacy practices in a grade 10 English classroom at a private school. - Skudowitz, Joanne (My University, 2009)
This study aimed to investigate the extent to which a class of grade 10 students at a private, co-educational school in Johannesburg, South Africa, are digitally literate and how they engage with digital technology both inside and outside the classroom. The study also aimed to explore some implications of these students‟ digital literacy practices for the teaching of English at the school. Data were collected from interviews and from questionnaires completed by the students. Students also wrote digital literacy histories. The main finding is that the participants in the study are digitally literate and engage with digital technology on a day-to-day basis. They are the lap generation (Tapscott, 1998) as they are lapping their parents and teachers with regard to their knowledge and use of digital technology. This use occurs primarily in their out-of-school, or social, environments and is not being drawn on substantively in the classroom, even in a well-resourced school.
Keywords: Digital literacy; English classroom